Questionário de qualidade de vida de crianças com paralisia cerebral (cp qol-child): tradução e adaptação para língua portuguesa - Braccialli, Lígia Maria Presumido [UNESP]; Braccialli, Ana Carla; Sankako, Andréia Naomi [UNESP]; Dechandt, Maria Luiza da Costa [UNESP]; Almeida, Vanessa da Silva [UNESP]; Carvalho, Sebastião Marcos de [UNESP] (My University, 2013)
The aim of this study was to verify the reliability of the Brazilian Portuguese version of the instrument Cerebral Palsy: quality of life questionnaire for children: primary caregiver questionnaire (CP QOLChild: primary caregiver) translated and culturally adapted. Thus, the translation and cultural adaptation of the instrument was made, and then the procedures to verify its reliability were performed. The translated and culturally adapted questionnaire was answered by 30 caregivers of children with cerebral palsy and inter and intra-observer analysis followed. The data allowed the authors to identify an internal consistency rangering from 0.649 to 0.858, intra-observer reliability from 0.625 to 0.809 and inter-observer reliability from 0.498 to 0.903. The analysis suggests that the instrument has acceptable psychometry.

O objetivo deste estudo foi verificar a confiabilidade da versão em português do Brasil do instrumento Cerebral Palsy: quality of life questionnaire for children: primary caregiver questionnaire (CP QOLChild: primary caregiver) traduzido e adaptado culturalmente. Para tanto, foi realizada a tradução e a adaptação cultural do instrumento e a seguir foram realizados os procedimentos para verificar a confiabilidade. O questionário traduzido e adaptado culturalmente foi respondido por 30 cuidadores de crianças com paralisia cerebral e realizada a análise inter e intraobservadores. Os dados permitiram identificar que consistência interna variou de 0,649 a 0,858, a confiabilidade intraobservador de 0,625 a 0,809 e a confiabilidade interobservador 0,498 a 0,903. A análise realizada sugere que o instrumento utilizado tem aceitabilidade psicométrica.
Quality of life questionnaire for children with cerebral palsy (cp qol-child): translation and cultural adaptation for brazilian portuguese language
Keywords: paralisia cerebral; qualidade de vida